2015
DOI: 10.2134/agronj14.0634
|View full text |Cite
|
Sign up to set email alerts
|

Management of Manure Nitrogen Using Cover Crops

Abstract: Th e experiment was conducted to determine whether cover crops reduce N losses of fall-applied liquid hog manure and whether sequestered N by cover crops is "transferred" to subsequent corn (Zea mays L. ] spring-killed, and no-cover crop), and three target manure rates (0, 100, and 200 kg N ha -1 ). Non-legume cover crops positively responded to fall manure application, where biomass increased by 50 to 130%. Red clover biomass increased 0 to 25% at higher manure rate application. A similar trend was found with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 42 publications
3
29
0
Order By: Relevance
“…A comparison of FWANC between SU168 and SU168NT+R treatments shows that the cover crop was effective in reducing NO 3 ‐N concentrations in drainage water but not total N losses. Cover crops have been shown to immobilize N and reduce mineral N levels in soil (Thilakarathna, Serran, Lauzon, Janovicek, & Deen, ), leading to less NO 3 ‐N leaching during the periods of high subsurface flow (Salmerón, Cavero, Quilez, & Isla, ). This can be particularly effective for reducing NO 3 ‐N leaching during periods of no N uptake by the cash crop and is the likely mechanism behind reduced NO 3 ‐N concentrations observed in this study.…”
Section: Resultsmentioning
confidence: 99%
“…A comparison of FWANC between SU168 and SU168NT+R treatments shows that the cover crop was effective in reducing NO 3 ‐N concentrations in drainage water but not total N losses. Cover crops have been shown to immobilize N and reduce mineral N levels in soil (Thilakarathna, Serran, Lauzon, Janovicek, & Deen, ), leading to less NO 3 ‐N leaching during the periods of high subsurface flow (Salmerón, Cavero, Quilez, & Isla, ). This can be particularly effective for reducing NO 3 ‐N leaching during periods of no N uptake by the cash crop and is the likely mechanism behind reduced NO 3 ‐N concentrations observed in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Spring and fall biomass values of RC in the current study were 4059 and 6796 kg ha −1 , which were greater than the values reported for RC (734–3140 kg ha −1 ) from a similar soil within ∼90 km of this field site (Coombs et al, 2017) as well as greater than the 690 to 4200 kg ha −1 reported in temperate climates (Snapp et al, 2005; Gaudin et al (2013, 2014). Coombs et al (2017) noted that when RC was left alive over winter, biomass was increased relative to the fall biomass in Ontario (Vyn et al, 2000; Gaudin et al, 2013; Thilakarathna et al, 2015) as well as in Ohio and Michigan (Henry et al, 2010; Gentry et al, 2013). Over winter increase of RC biomass also occurred in this study with the average biomass of 4059 kg ha −1 in the fall increasing to 6796 kg ha −1 in the following spring.…”
Section: Resultsmentioning
confidence: 99%
“…From 100-199 kg·N/ha the productivity was boosted by 17%, and at 200 kg·N/ha or higher there was no significant impact [4]. Thilakarathna et al support this finding with their study comparing legume and non-legume cover crops [65]. Furthermore, in a corn-soybean intercrop, Martin et al found that a moderate fertilizer application rate (60 kg/ha, rather than 0 kg/ha or 120 kg/ha) maximized corn yield without suppressing nodulation in soybeans [62].…”
Section: Nitrogen Use Efficiencymentioning
confidence: 88%
“…In corn crops, nitrogen intake peaks between the sixth and eighth collar and is low after silking [64]. With the hindrance of decomposition over winter in Ontario, as well as the time needed for corn germination and emergence, the timing of red clover's nitrogen release seems to correspond aptly with corn development needs [65].…”
Section: Nitrogen Use Efficiencymentioning
confidence: 99%